2014
DOI: 10.1155/2014/418624
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Inhibit VEGF165-Induced Migration and Tube Formation of Endothelial Cells via the Akt Pathway

Abstract: The early stages of angiogenesis can be divided into three steps: endothelial cell proliferation, migration, and tube formation. Vascular endothelial growth factor (VEGF) is considered the most important proangiogenic factor; in particular, VEGF165 plays a critical role in angiogenesis. Here, we evaluated whether gold nanoparticles (AuNPs) could inhibit the VEGF165-induced human umbilical vein endothelial cell (HUVEC) migration and tube formation. AuNPs and VEGF165 were coincubated overnight at 4°C, after whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 31 publications
3
73
1
Order By: Relevance
“…26 Pan et al demonstrated that gold NP inhibited HUVEC VEGF165-induced migration and tube formation. 27 On the contrary, neither HYA-PHMB-NC nor PLLA-OCT-NP used in the present studies exhibited any effect on the formation of microcapillary-like structures in the NP-treated co-cultures compared to the untreated co-culture. Thus, angiogenesis, one of the most important factors in the wound healing process, is not influenced by the presence of the nanocompounds, further demonstrating their high tissue compatibility.…”
Section: Discussioncontrasting
confidence: 65%
“…26 Pan et al demonstrated that gold NP inhibited HUVEC VEGF165-induced migration and tube formation. 27 On the contrary, neither HYA-PHMB-NC nor PLLA-OCT-NP used in the present studies exhibited any effect on the formation of microcapillary-like structures in the NP-treated co-cultures compared to the untreated co-culture. Thus, angiogenesis, one of the most important factors in the wound healing process, is not influenced by the presence of the nanocompounds, further demonstrating their high tissue compatibility.…”
Section: Discussioncontrasting
confidence: 65%
“…13 Our previous studies showed that monotherapy by AuNPs reduced angiogenesis in liver tumors 14 and inhibited VEGF165-induced human umbilical vein endothelial cell (HUVEC) migration and tube formation via the Akt pathway. 15,16 In this study, we aimed to investigate the mechanism of AuNPs in reducing melanoma lung metastasis. Immunofluorescence and immunohistochemistry were carried out to evaluate the vascular morphology, perfusion, permeability and hypoxia in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent toxicological studies with cell cultures have shown the ability of AuNP to decrease cell viability and proliferation of microvascular endothelial cells (61). Similarly, human umbilical vein endothelial cells exposed to AuNP presented decreased levels of vascular endothelium growth factor (VEGF) (62). VEGF, a major angiogenic factor, also promotes endothelial cell migration and proliferation and may initiate the signaling cascade leading to nitric oxide (NO) production (63).…”
Section: Examples Of Enm Vascular Toxicitymentioning
confidence: 99%
“…It is noteworthy that modulation of VEGF signaling is a recurring theme in the antiangiogenic effects of metallic ENM. Increasing evidence suggests that this effect may occur due to inhibition of phosphorylation of associated downstream effector molecules including Src (83) and Akt (62), which could lead to increased endothelial cells apoptosis (84), impaired hematopoietic cell development, survival, differentiation, and migration (85–87) as well as aberrant vasculogenesis and heart development in prenatally exposed subjects (87). …”
Section: Examples Of Enm Vascular Toxicitymentioning
confidence: 99%